Fibroblast growth factor receptor 4 gene (FGFR4) 388Arg allele predicts prolonged survival and platinum sensitivity in advanced ovarian cancer - Marmé, Frederik; Hielscher, Thomas; Fastner, Sarah; Bondong, Sandra; Ferschke, Irmgard; Rom, Joachim; Sohn, Christof; Schneeweiss, Andreas; Altevogt, Peter (International journal of cancer, 2012)
FGFR4 has been shown to play an important role in the etiology and progression of solid tumors. A single nucleotide polymorphism (SNP) within the FGFR4 gene has previously been linked to prognosis and response to chemotherapy in breast cancer and other malignancies. This study evaluates the relevance of this SNP in advanced ovarian cancer. FGFR4-genotype was analyzed in 236 patients recruited as part of the OVCAD project. Genotyping was performed on germ-line DNA using a TaqMan based genotyping assay. Results were correlated with clinicopathological variables and survival. The FGFR4 388Arg genotype was significantly associated with prolonged progression-free and overall survival (univariate: HR 0.68, p = 0.017; HR 0.49, p = 0.005; multivariate: HR 0.69, p = 0.025; HR 0.49, p = 0.006) though the positive prognostic value was restricted to patients without postoperative residual tumor. Indeed, there was a significant interaction between FGFR4 genotype and residual tumor for overall survival. Furthermore, the FGFR4 388Arg genotype significantly correlated with platinum sensitivity in the same subgroup (multivariate OR 3.81 p = 0.004). FGFR4 Arg388Gly genotype is an independent and strong context specific prognostic factor in patients with advanced ovarian cancer and could be used to predict platinum-sensitivity.
First published 27 October 2011
Gesehen am 04-10-2018